Analisis Segmentasi, Targeting, Positioning Dalam Upaya Meningkatkan Minat Beli Produk di Adorable Project Cimahi Jawa Barat - Maulidina, Emylia; Tiris Sudrartono (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
AdorableProject is one of the fashion brands in Cimahi City, West Java that sells women's fashion products, such as footwear, bags and other accessories. AdorableProject has several strategies implemented to increase and expand marketing as well as product buying demand. This study uses qualitative and descriptive methods to find out how the company's efforts in increasing product buying interest with segmentation, targeting and positioning strategies (STP). Based on the results of the study, AdorableProject experienced an increase and decrease in product sales in 2022. The drastic decrease in 2022 occurred in May by 56.92%, this illustrates that the level of product buying interest in AdorableProject is not significant. Determination of segmentation, targeting and positioning. In segmentation analysis, it is formed based on 4 segments, namely geographical segmentation, demographic segmentation, psychographic segmentation, behavioral segmentation. It can determine the target market's goals. Positioning that is formed based on consumer assessment of the marketing mix. Marketing efforts made by the company are by selling products offline. This can increase purchasing interest in the product.